Novel hormonal agents in men with metastatic castration resistant prostate cancer and reduced performance status: Experiences of a specialized single center - Thomas Büttner; Philipp Lossin; Stefan Latz; Carolin Jacobs; Philipp Krausewitz; Stefan Hauser (Aging Medicine)
Abstract Objectives Attaining castration resistance in metastatic prostate cancer (mCRPC) represents a pivotal juncture in the progression of the patient's illness and treatment regimen. Within this therapeutic context, novel hormonal agents (NHA) constitute a fundamental component of pharmacological intervention. However, the efficacy of NHA therapy remains uncertain for patients with a compromised general condition, as indicated by an Eastern Cooperative Oncology Group Performance Status (ECOG PS) score of ≥2. Notably, most clinical trials excluded individuals with an ECOG PS ≥2, leaving a gap in our understanding of the potential benefits of NHA therapy for this specific patient cohort. Methods We conducted an analysis of fifty‐three NHA‐naïve men characterized by attaining mCRPC at an ECOG PS of ≥2 subsequent to androgen deprivation monotherapy between 2008 and 2023. Patients were then treated with either NHA or Best Supportive Care (BSC) based on individual decisions. Survival and adverse event (AE) analysis was performed to assess the outcomes of NHA therapy compared to BSC. Results Among the patients, 30 (56.6%) received NHA, whereas the remaining 23 (43.4%) choose BSC. No significant differences in baseline characteristics were observed between the NHA and BSC group. Median overall survival (OS) was 9.1 months in the BSC group and 7.0 months in the NHA group, with no significant OS benefits associated with NHA treatment. AEs and severe AEs commonly occurred, but remained indifferent between treatment groups. Conclusions Our findings suggest that NHA therapy may confer reduced survival benefits in mCRPC patients with ECOG PS ≥2. While hope for NHA treatment persists, particularly given its oral administration and tolerability, careful consideration and discussion with patients regarding treatment expectations and palliative care goals are warranted in this challenging patient population.